2021
DOI: 10.1111/jce.15288
|View full text |Cite
|
Sign up to set email alerts
|

The established and the challenger: A direct comparison of current cryoballoon technologies for pulmonary vein isolation

Abstract: Introduction: Cryoballoon (CB) ablation for pulmonary vein isolation (PVI) is an effective treatment of atrial fibrillation (AF). Recently, a novel cryoablation system was introduced. The aim of the study was to compare the safety, efficacy and biophysical characteristics of a novel cryoablation system (POLARx™; Boston Scientific) to a commonly used and clinically well characterized system (Arctic Front Advance Pro™, AFA; Medtronic). Methods and Results: Fifty consecutive patients with symptomatic AF, who unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(38 citation statements)
references
References 13 publications
(23 reference statements)
5
32
1
Order By: Relevance
“…Heterogeneity for the outcome of first freeze isolation LIPV was driven primarily by the study of Guckel et al [13] After the exclusion of this study, no difference between was detected in the likelihood of first freeze isolation LIPV (P = 0.16) (Supplemental figure S5 A). Heterogeneity for the outcomes of TTI recording LSPV, TTI LSPV and TTI RSPV was driven primarily by the study of Moser et al [16] After the exclusion of this study, TTI recording LSPV and TTI LSPV became in favour of POLARx (P = 0.004 and P = 0.02, respectively) (Supplemental figure S5 B and S5C). Furthermore, sensitivity analysis demonstrated that TTI RSPV became in favour of AFA-Pro after the exclusion of the study of Moser et al (P < 0.001) (Supplemental figure S5 D).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Heterogeneity for the outcome of first freeze isolation LIPV was driven primarily by the study of Guckel et al [13] After the exclusion of this study, no difference between was detected in the likelihood of first freeze isolation LIPV (P = 0.16) (Supplemental figure S5 A). Heterogeneity for the outcomes of TTI recording LSPV, TTI LSPV and TTI RSPV was driven primarily by the study of Moser et al [16] After the exclusion of this study, TTI recording LSPV and TTI LSPV became in favour of POLARx (P = 0.004 and P = 0.02, respectively) (Supplemental figure S5 B and S5C). Furthermore, sensitivity analysis demonstrated that TTI RSPV became in favour of AFA-Pro after the exclusion of the study of Moser et al (P < 0.001) (Supplemental figure S5 D).…”
Section: Resultsmentioning
confidence: 99%
“…1 ). [8] , [9] , [10] , [11] , [13] , [14] , [15] , [16] All included studies were observational in design and found to be of good quality based on the Newcastle Ottawa scale (Supplemental table S1 ).
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations